REALITY OF THE ACTIVITIES CARRIED OUT BY EXTENSION FARMS PROVIDING EXTENSION SERVICES TO THE FARMERS OF THE CENTRAL EUPHRATES PROVINCES - Twayej , S. A.; Al-Taiy, H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed  to identify the reality of the extension farm activities in providing extension services to the farmers of the middle Euphrates governorates. The study was   included 54 paragraphs divided into 3 axes outline  which included: extension activities implemented inside the extension farm, extension activities implemented outside the extension farm, coordination activities and participation with relevant institutions. A random sample of 60% of the extension farms in each governorate was selected using a questionnaire from a random sample of 41 respondents. The research results were activities of applying scientific research results, with a degree of 1.4 degrees which is less than the hypothetical mean for the scale of 1.5 degrees, and activities of multiplication program of high-class seeds , with a degree of 55%. The activities of using modern means of communication, with a degree of 1.1, and activities to encourage agricultural innovation, with a degree of 1.4,which is less than the hypothetical mean for the scale of 1.5 degrees. The activities of interaction with stakeholders, with a degree of 2.55, which is higher than the hypothetical mean for the scale of 2.5 degrees ,and coordination activities or partnerships with a degree of 1.2, which is less than the hypothetical mean for the scale of 1.5 degrees. It could be concluded from the results that weakness of the various extension farm activities inside and outside its borders, and in the activities of coordination and participation.